A Heuristic Approach to Render Ray Tracing Effects in Real Time for First-Person Games - Andrade, Paulo; Clua, Esteban; Sabino, Thales; Forti, Fabio (Journal on Interactive Systems, 2014)
Realistic computer graphics effects as mirror reflections, transparency, caustics and detailed shadows are hard to simulate using real time raster based rendering, since they require global illumination approaches. One option is ray trace these effects using a real-time hybrid renderer, where ray tracing and raster rendering are used together to generate the best visual experience. Unfortunately, the ray tracing stage of a hybrid renderer can be a very demanding stage, making it hard to maintain real time frame rates in virtual environments where many elements must be ray traced. This work present a heurist to select the best subset of elements to ray trace in real time, in a hybrid renderer, in order to improve the visual experience offered by an equivalent raster only render, and still maintain the real time experience. The selection process considers rendering time constraints, spatial information of the environment, previous elements selected for ray tracing and current information about the candidate elements.